ANTIOXIDANT ACTIVITY FOR FREE RADICAL SCAVENGING IN CAESALPINIA SAPPAN WITH LEAF EXTRACTS - REVATHI, K.; ADELINE, JOSEPHINE (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
Plants are the natural source provided by our nature. Nature has bestowed us With numerous of herbal medicines as they synthesis with therapeutic experiences of generations for practicing medicines for over hundreds of years. More than 80% of the world's population relies on traditional medicine for their primary healthcare needs. In this research paper investigations were carried out using the leaf extracts of Caesalpinia sappan. Five major solvents were used namely ethanol, acetone, aqueous, chloroform and petroleum ether. Antioxidant activity was carried out for scavenging free radicals using DPPH method using qualitative and quantitative analysis. Further, the results concluded that maximum amount of antioxidant activity was found in ethanol extracts followed by the other solvents. Thus the leaf extracts of Caesalpinia sappan had the high quality of possessing the antioxidant activity.